2019
DOI: 10.1016/j.drugalcdep.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive accuracy and interoceptive sensibility in individuals with alcohol use disorder–Different phenomena with different clinical correlations?

Abstract: Background: Interoception may contribute to substance use disorder as it relates to the body's experience of substance use or withdrawal. However, only a few studies have directly investigated associations between interoception and alcohol use. The objective of this study was to compare individuals with alcohol use disorder (AUD) and healthy controls on interoceptive sensibility and accuracy. Methods: The sample was comprised of two groups: individuals meeting criteria for AUD (N = 114) and healthy controls (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…On the other hand, adolescents diagnosed with substance use disorder demonstrated altered insula response to pleasant interoceptive stimuli (14). Prior work indicates that individuals with AUD are characterized by lower interoceptive accuracy and higher sensibility in comparison to healthy controls (6). In this sample, interoceptive sensibility was also associated with high levels of anxiety, depression, and more severe sleep problems.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…On the other hand, adolescents diagnosed with substance use disorder demonstrated altered insula response to pleasant interoceptive stimuli (14). Prior work indicates that individuals with AUD are characterized by lower interoceptive accuracy and higher sensibility in comparison to healthy controls (6). In this sample, interoceptive sensibility was also associated with high levels of anxiety, depression, and more severe sleep problems.…”
Section: Introductionmentioning
confidence: 72%
“…However, to the best of our knowledge, associations between emotion regulation and interoception have not been investigated among individuals with AUD. This could have utility given the significance of both interoception and emotion regulation within this clinical sample (6,20). Moreover, evidence for a common neurobiological underpinning for processes associated with interoception, emotion regulation, and craving lend support to a plausible connection between these constructs.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…For example, aside from the panic disorder studies already discussed, a recent review concluded that—while work to date has a number of important limitations—the cumulative evidence suggests that individuals with moderate depression symptoms appear to show impaired interoceptive accuracy 45 . Other preliminary work has also linked alcohol use disorder with low interoceptive accuracy 46 , and there are several neuroimaging studies suggesting altered interoceptive processing within substance users 33 , 47 49 . Thus, we sought to confirm whether our hypothesized interoceptive processing deficit was present across these diagnostic categories.…”
Section: Introductionmentioning
confidence: 99%